Neurocognitive effects of agomelatine treatment in schizophrenia patients suffering from comorbid depression: results from the AGOPSYCH study - Englisch, Susanne Angelika; Meyer-Lindenberg, Andreas; Zink, Mathias (Journal of clinical psychopharmacology, 2018)
AbstractBackgroundCognitive impairment in schizophrenia is highly disabling and remains one of the major therapeutic challenges. Agomelatine (AGO), an agonist at melatonergic MT1/MT2 receptors and antagonist at 5-HT2C receptors, increases dopamine and norepinephrine in the prefrontal cortex and may